Evolution of endovascular stroke therapies and devices. (3rd March 2016) - Wallace, Adam N; Kansagra, Akash P; McEachern, James; Moran, Christopher J; Cross III, Dewitte T; Derdeyn, Colin P
SUMMARY: Acute ischemic stroke is caused by occlusion of a cerebral artery, resulting in loss of brain tissue and neurologic deficits. However, a portion of the ischemic brain can be salvaged if blood flow is restored within an appropriate time frame. The past year has seen the publication of five positive randomized controlled trials demonstrating substantial benefit of mechanical thrombectomy in select patients with large vessel cerebrovascular occlusion. This progress is related to several factors, but most importantly, dramatic improvements in speed and rates of recanalization with the latest generation devices. In this article, we review the evolution of endovascular acute ischemic stroke therapies and key design features of the most widely used devices.